2005
DOI: 10.1038/sj.cr.7290347
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Survivin and CDK4 by Epstein-Barr virus encoded latent membrane protein 1 in nasopharyngeal carcinoma cell lines

Abstract: Latent membrane protein 1 (LMP1), an important protein encoded by Epstein Barr virus (EBV), has been implied to link with the pathogenesis of nasopharyngeal carcinoma (NPC). Its dual effects of increasing cell proliferation and inhibiting cell apoptosis have been confirmed. In this study, we showed that the expression of Survivin and CDK4 protein in CNE-LMP1, a LMP1 positive NPC epithelial cell line, is higher than in LMP1 negative NPC epithelial cell line-CNE1, and the expression is LMP1 dosage-dependent. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Cyclin D1 and P16 eventually influence the G 1 –S checkpoint by interacting with CDK4 29. By co-immunoprecipitation, western blot using the nuclear and cytoplasmic extracts and immunolabelling confocal assays, we found that CDK4 was co-immunoprecipitated with survivin in P16-deficient HCC cells, both co-localised mainly in cancer cell nuclei.…”
Section: Discussionmentioning
confidence: 84%
“…Cyclin D1 and P16 eventually influence the G 1 –S checkpoint by interacting with CDK4 29. By co-immunoprecipitation, western blot using the nuclear and cytoplasmic extracts and immunolabelling confocal assays, we found that CDK4 was co-immunoprecipitated with survivin in P16-deficient HCC cells, both co-localised mainly in cancer cell nuclei.…”
Section: Discussionmentioning
confidence: 84%
“…LMP1 protein is a ligand-independent tumor necrosis factor receptor, which can activate many mammalian signal transduction pathways mediated by three activation regions, 1, 2 and 3 (CTAR1, CTAR2 and CTAR3), in the C-terminal (Pai and Khanna, 2001;Kieser, 2008;Munz and Moormann, 2008). Among them, CTAR1 domain has a critical role in LMP1-induced tumor transformation and accelerates G1/S transition in NPC cells through activation of nuclear factor-kB and mitogen-activated protein kinase signaling and upregulated expression of cell cycle regulators, such as CDK4, cyclin D1, E2F1 and survivin (Tsao et al, 2002;Ai et al, 2005;Soni et al, 2007;Zheng et al, 2007;Demetriades and Mosialos, 2009), although the detailed mechanisms remain elusive. In this study, we found that LMPIP was one of the important mediators of LMP1 leading to decreased cellular ROS generation and shortened G1/S phase transition through the mitogen-activated protein kinase (extracellular signal-regulated kinase 1/2) and nuclear factor-kB signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent with these findings, LMP1 was independently shown to enhance the expression of survivin (BIRC5) and Cdk4 in CNE cells in a dose-dependent fashion, whilst also inducing their interaction in the nucleus [66]. LMP1 was also found to downregulate the expression of the retinoic acid receptor b2 (RARb2) in NPC cells via upregulation of DNA methyl transferases (DNMTs) 1, 3a and 3b, resulting in RARb2 promoter hypermethylation [67].…”
Section: Deregulation Of Cell-cycle Checkpoint Controlsmentioning
confidence: 91%